The submission - Waldman, Amy (London : Windmill Books, 2012)
A jury gathers in Manhattan to select a memorial for the victims of a devastating terrorist attack. Their fraught deliberations complete, the jurors open the envelope containing the anonymous winner's name - and discover he is an American Muslim. Instantly they are cast into a roiling debate about the claims of grief, the ambiguities of art, and the meaning of Islam. Their conflicted response is only a preamble to that of the country
Fiction
ENH
Karim International
Keywords: September 11 Terrorist Attacks (2001) -- Social aspects -- Fiction; Memorials -- Fiction; English literature